Experimental study on the influence of porous foam metal filled in the core flow region on the performance of thermoelectric generators. (1st December 2017) - Li, Yanzhe; Wang, Shixue; Zhao, Yulong; Lu, Chi
Highlights: Experiment using TEG to recover the exhaust heat of automobile is performed. Foam metal is applied to improve the efficiency of TEG. Core flow heat transfer enhancement is used to improve the efficiency of TEG. The effect of different PPI foam metal on the TEG has been analyzed. Abstract: Semiconductor thermoelectric generator technology is a new type of power generation technology. The use of semiconductor thermoelectric power generation technology for automobile exhaust heat recovery and utilization can effectively improve energy efficiency. In this study, a test system is set up to simulate the automobile exhaust, and the effect of core flow heat-transfer enhancement on the performance of the thermoelectric generator is investigated using thermoelectric module Bi2 Te3 to recover the waste heat from automobile exhaust and convert it into electrical energy. The results show that filling foam metal can significantly improve the performance of the generator. The convective heat-transfer coefficient of the channel increases by four times, and the output power of the thermoelectric generator is doubled when the intake flow rate is 120 m 3 /h, the inlet temperature is 300 °C, the pore density of the foam metal is 20 pores per inch, and the filling rate of the foam metal is 75%. In addition, the improvement in the performance of the generator is different under different intake air flows, different foam-metal filling rates, and different pore densities.